Socio-Emotional Skills in Educational Communities: Contributions to Integral Teacher Training - Aristulle, Patricia del Carmen (2019)
This study is aimed at describing and analyzing the role that emotions play on socioeconomic skills within an educational community as executed San Jose Primary School Teachers College in Cordoba, Argentina (Profesorados de Educación Inicial y de Educación Primaria del Instituto Superior de Formación Docente San José). This institute possesses a favorable learning environment that surpasses traditional prescriptive curriculums which include the development of socioemotional skills, a topic that has a positive impact on the composition of an educational community. We may ask ourselves, How are teachers preparing for the future in considering such teaching and learning perspectives within their scope of work? How will they broadly exceed the cognitive skills and place socioemotional skills as an important priority of their skillset? This study prompts us to reflect on the complexity of learning and aims to contribute to broadening the teaching horizons of teachers. Within this framework, the socioemotional skills of teachers in training was surveyed through a questionnaire. The results are considered promising in order to open spaces for reflection on the role that this type of skills should play in the new didactic agenda. Thus, the obtained findings challenge us to revise the curricular designs that guide teacher training to identify contributions capable of impacting their socio-emotional skills and promote the development of educational communities. The results are considered to be promising since they open spaces for reflection on the role that these types of skills could play in the new didactic agenda. Thus, the obtained findings challenge us to revise curricular designs that guide teacher training to identify contributions that will foster the development of their socio-emotional skills and promote the evolution of educational communities.